Health care workers' perceptions and bias toward men as HIV clients in Malawi and Mozambique: A qualitative study. - Kathryn Dovel; Rose Paneno; Kelvin Balakasi; Julie Hubbard; Amílcar Magaço; Khumbo Phiri; Thomas Coates; Morna Cornell (PLOS Global Public Health)
Men are underrepresented in HIV services throughout sub-Saharan Africa. Little is known about health care worker (HCW) perceptions of men as clients, which may directly affect the quality of care provided, and HCWs' buy-in for male-specific interventions. Focus group discussions (FGDs) were conducted in 2016 with HCWs from 15 facilities across Malawi and Mozambique and were originally conducted to evaluate barriers to universal treatment (not HCW bias). FGDs were conducted in local languages, recorded, translated to English, and transcribed. For this study, we focused on HCW perceptions of men as HIV clients and any explicit bias against men, using inductive and deductive coding in Atlas.ti v.8, and analyzed using constant comparison methods. 20 FGDs with 154 HCWs working in HIV treatment clinics were included. Median age was 30 years, 59% were female, and 43% were providers versus support staff. HCWs held strong explicit bias against men as clients. Most HCWs believed men could easily navigate HIV services due to their elevated position within society, regardless of facility-level barriers faced. Men were described in pejorative terms as ill-informed and difficult clients who were absent from health systems. Men were largely seen as "bad clients" due to assumptions about men's 'selfish' and 'prideful' nature, resulting in little HCW sympathy for men's poor use of care. Our study highlights a strong explicit bias against men as HIV clients, even when gender and bias were not the focus of data collection. As a result, HCWs may have little motivation to implement male-specific interventions or improve provider-patient interactions with men. Framing men as problematic places undue responsibility on individual men while minimizing institutional barriers that uniquely affect them. Bias in local, national, and global discourses about men must be immediately addressed.